An empirical investigation of the directivity of external industrial noise sources - Diamandopoulos, Jimmy; Larsson, Jimmy (My University, 2005)
This thesis work deals with the directivity of external industrial noise sources. The purpose is to investigate the possibility of making measurements with consideration to the directivity of these types of sources, and using this knowledge as a basis for the possibility of taking measures for reduction of sound pressure levels at specified points of perception. The objectives are to illustrate the concept of directivity and to show, by performing measurements on real sources, that there are actual differences when the directivity is regarded during measurements and when it is not. This will be shown empirically through measurements on a number of typical external industrial noise sources and by an analysis based on the results from these measurements. A method for implementation of the measurements methods described in standards ISO 3744-2, ref. 1 and DIN 45635-47, ref. 2, relevant for this work, has also been developed within the extent of this project.It has, by the use of empirical methods, been investigated that there are significant differences in the results received without consideration of directivity and the result received when the directivity has been considered. Also, the method, developed by us for the purpose of making measurement (with regards to directivity) possible to implement in reality, worked as intended. Also, it has been shown that one, with the use of simplified methods, can perform measurements in only one direction and achieve correct results, but without the knowledge of the directivity one looses the advantages of redirecting the source.
Keywords: Samhällsbyggnadsteknik; Civil Engineering